Evaluating rainbowing for ocean alkalinity enhancement - Bianchi, Riccardo; Abbate, Samuele; Lockley, Andrew; Abba', Antonella; Campo, Francesco; Varliero, Selene; Grosso, Mario; Caserini, Stefano (Environmental Research Communications, 2024)
Ocean Alkalinity Enhancement (OAE) is a technique proposed to address ocean acidification and global warming. This study examines rainbowing (i.e. water jets pumped into the air from ships) for the slaked lime slurry distribution. The fluid dynamic behaviour-both the in-air trajectory and subsurface-was studied using the Smoothed Particle Hydrodynamics method. Various outflow velocities were simulated for calm seas; different dilution factors and environmental slaked lime concentration spikes have been found. Linking slurry concentration to pH, discharge conditions that avoid damage to marine biota have been identified. A preliminary cost analysis compares rainbowing to ship-wake discharge. Rainbowing requires high power consumption to project large volumes of water far from ships. Very high dilution is needed, mainly because of the artificial requirement not to momentarily exceed 24-hour environmental pH limits; the effect of ocean turbulence on instantaneous pH peaks is negligible and is not considered in the analysis. Emissions due to energy consumption almost equalize carbon dioxide removed during discharge, making the method inefficient (only 176 kg of CO2 removed per ton of slaked lime spread). Previous ship-wake discharge analysis shows greater OAE performance and lower cost (5.5 versus 388 per ton of CO2 removed). In conclusion-based on the conservative environmental limits imposed, and the specific modeling undertaken-rainbowing is not demonstrated as an efficient method for OAE.